Assessment of blooming Ulva macroalgae production potential in the Yellow Sea, China. Issue 5 (3rd September 2019) - Cui, Jianjun; Zhang, Jianheng; Monotilla, Alvin P.; Huo, Yuanzi; Shi, Jinting; Zhao, Xiaohui; Kang, Xinyu; He, Peimin
ABSTRACT: Since 2007, large-scale blooms have periodically broken out in the Yellow Sea, leading to serious economic and ecological problems in the surrounding coastal environments. Previous studies reported that the blooms originated in the Rudong oceanic area of the southern Yellow Sea and drifted almost 400 km into the Qingdao oceanic area of the northern Yellow Sea. In this study, chlorophyll concentrations, chlorophyll fluorescence, growth rates, and reproductive characteristics of floating Ulva prolifera collected along the Yellow Sea coast were assessed. The results revealed that these four physiological parameters in the Rudong area at the bloom source were considerably higher (2.02 mg/g, 0.68, 28.49% d −1, and 4 × 10 7, respectively) than in the Qingdao area (0.34 mg/g, 0.31, 5.23% d −1, and 0.67 × 10 7, respectively). However, the abundance of microscopic propagules of Ulva in the Qingdao area (3980 ind/l) was significantly higher than that in the Rudong area (667 ind/l). These findings help increase our understanding of the formation of the world's largest Ulva macroalgal blooms.